2020
DOI: 10.3390/diagnostics10100769
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Targeted Library Preparation Solutions for SARS-CoV-2 Whole Genome Analysis

Abstract: Single next-generation sequencing (NGS) proved to be an important tool for monitoring the SARS-CoV-2 outbreak at the global level Until today, thousands of SARS-CoV-2 genome sequences have been published at GISAID (Global Initiative on Sharing All Influenza Data) but only a portion are suitable for reliable variant analysis. Here we report on the comparison of three commercially available NGS library preparation kits. We discuss advantages and limitations from the perspective of required input sample quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Additional modifications such as DNA-rehybridization steps 25 or slower temperature ramp speeds had no significant effects (Sup Fig 4c, 4d) . We found that an alternative primer design using shorter (~150bp) amplicons, the Paragon Genomics CleanPlex SARS-CoV-2 panel, did recover more complete genomes in very low viral load samples (CT >35), but had lower accuracy and drops in coverage even in high viral load samples which resulted in missed SNV calls ( Sup Fig 3a, 3b ), consistent with previous reports 12,26 . In our hands, a 40 cycle PCR utilizing ARTIC primers without alterations to the ramp temperatures or speeds provided the greatest amplification without deleterious effects of increasing unfounded SNV calls.…”
Section: Resultssupporting
confidence: 90%
“…Additional modifications such as DNA-rehybridization steps 25 or slower temperature ramp speeds had no significant effects (Sup Fig 4c, 4d) . We found that an alternative primer design using shorter (~150bp) amplicons, the Paragon Genomics CleanPlex SARS-CoV-2 panel, did recover more complete genomes in very low viral load samples (CT >35), but had lower accuracy and drops in coverage even in high viral load samples which resulted in missed SNV calls ( Sup Fig 3a, 3b ), consistent with previous reports 12,26 . In our hands, a 40 cycle PCR utilizing ARTIC primers without alterations to the ramp temperatures or speeds provided the greatest amplification without deleterious effects of increasing unfounded SNV calls.…”
Section: Resultssupporting
confidence: 90%
“…Among the many approaches available for SARS-CoV-2 whole-genome analysis, the amplicon-based sequencing method developed by the ARTIC Network [ 27 ] is currently the most widely used [ 13 , 24 , [28] , [29] , [30] , [31] , [32] ]. Based on the PrimalSeq protocol originally developed for Zika virus [ 23 , 33 ], the ARTIC Network designed a set of 98 tiled amplicons in two PCR pools for the targeted whole-genome amplification of SARS-CoV-2 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity, specificity and limit of detection are dependent of the chosen method (15). Amplicon-based methods are the most widely used approach for SARS-CoV-2 genotyping due to their relative low cost and simplicity (16-22). Despite their widespread use, amplicon-based technologies are associated with source-specific factors that, if not accounted for, can affect the reliability of assigned genotypes (11-14) and impact, for example, the measurements of viral intra-host variability (23).…”
Section: Introductionmentioning
confidence: 99%